Gender Comparison of Image Perception and Preferences for Spring • Summer Shirt Yarn-dyed Fabrics (Journal of Fiber Bioengineering and Informatics, 2015)
The research proposes to extract data of male and female consumers' image perception and preferences\rin yarn-dyed fabrics for spring and summer shirts. The Semantic Differential (SD) evaluation on\rrepresentative fabric samples by two groups of subjects was accomplished following the standardized\rsensory evaluation procedures. The differences in terms of image perception in yarn-dyed fabrics between\rmale and female subjects was identified through Levene homogeneity variance test and independent\rsamples T-test, and the evaluation factors of subjects' image perception was classified into 6 factors\rthrough factor analysis. The relationships between image word-pairs and subjects' preferences were\rvalidated with regression analysis. Experiment results show an evident difference in terms of image\rperceptions, preferences and the factors affecting preferences of the yarn-dyed fabrics between male\rand female subjects. The quantitative data could consequently provide guidance to help designing and\rproducing differentiated yarn-dyed fabrics for designated sex consumers.